Performance investigation of a head-operated device and expanded membrane cursor keys in a target acquisition task. - Capilouto GJ; Higginbotham DJ; McClenaghan B; Williams HG; Dickerson J (Technology & Disability, 2005)
This study investigated the relative performance of two computer input devices appropriate for persons sharing similar motor challenges: a head operated device and expanded membrane cursor keys. Performance was evaluated in the context of a Fitts' law target acquisition task. For this initial phase of investigation, subjects without disabilities were selected to focus on performance differences inherent in the devices and their operation. Results indicated that the total time to acquire a target was significantly faster for the head device than for the expanded cursor keys. For typical young adults, the head-operated device required less time to reach asymptote performance by simplifying the cognitive demands for device operation. These results suggest that for persons unable to isolate their fingers, head-operated controls may offer advantages over input devices operated by the upper extremities.